2014
DOI: 10.3109/17453674.2014.885356
|View full text |Cite
|
Sign up to set email alerts
|

Posterior approach and uncemented stems increases the risk of reoperation after hemiarthroplasties in elderly hip fracture patients

Abstract: BackgroundHemiarthroplasties are performed in great numbers worldwide but are seldom registered on a national basis. Our aim was to identify risk factors for reoperation after fracture-related hemiarthroplasty in Norway and Sweden.Material and methodsA common dataset was created based on the Norwegian Hip Fracture Register and the Swedish Hip Arthroplasty Register. 33,205 hip fractures in individuals > 60 years of age treated with modular hemiarthroplasties were reported for the period 2005–2010. Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 37 publications
5
98
1
3
Order By: Relevance
“…A large registry study with unadjusted covariates found a high prevalence of preoperative neurologic conditions in patients who experienced dislocation after bipolar arthroplasty [22]. Another large registry study reported that using the posterior surgical approach increased the risk of reoperation as a result of dislocation in elderly patients with hip fracture [20], however, this study did not distinguish between unipolar and bipolar hemiarthroplasties. Another study showed that postoperative global femoral offset and limb length discrepancy were risk factors for prosthetic dislocation after hemiarthroplasty through the posterolateral approach for femoral neck fracture [17].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…A large registry study with unadjusted covariates found a high prevalence of preoperative neurologic conditions in patients who experienced dislocation after bipolar arthroplasty [22]. Another large registry study reported that using the posterior surgical approach increased the risk of reoperation as a result of dislocation in elderly patients with hip fracture [20], however, this study did not distinguish between unipolar and bipolar hemiarthroplasties. Another study showed that postoperative global femoral offset and limb length discrepancy were risk factors for prosthetic dislocation after hemiarthroplasty through the posterolateral approach for femoral neck fracture [17].…”
Section: Introductionmentioning
confidence: 58%
“…These are major complications of hip arthroplasty performed on patients with displaced femoral neck fractures [1,22]. The posterior surgical approach clearly increases the risk of dislocation, as supported by several clinical studies on patients with hip fracture [6,19,20]. Enocson et al [6] reported a higher dislocation proportion of 13% using the posterolateral approach than the 3% with the anterolateral approach in 720 patients with femoral neck fractures, and Pajarinen et al [19] reported a 16% dislocation rate after surgery through the posterior approach compared with 7% after the anterior approach in 338 hip fracture surgeries.…”
Section: Discussionmentioning
confidence: 96%
“…27 Posterior approaches have a higher dislocation risk of hemiarthroplasty when compared to anterolateral approaches. 95 In total hip arthroplasty, increasing the head size decreases dislocation risk. Risk of dislocation after total hip arthroplasty for hip fracture is thought to be higher than after total hip arthroplasty for osteoarthritis.…”
Section: Arthroplasty-related Complicationsmentioning
confidence: 99%
“…Rates of infection after hemiarthroplasty for hip fracture have been reported at 1.3% in the Scandinavian database. 95 Infections can occur immediately after the procedure or later. The patient with a wound that does not heal or continues to drain after hip replacement is likely to have infectious process.…”
Section: Arthroplasty-related Complicationsmentioning
confidence: 99%
“…A review of over 33 000 hemiarthroplasties of Swedish and Norwegian hip registries showed that posterior approach and use of uncemented stems was associated with increased reoperation rates. 19 Further, it has been suggested that bipolar prosthesis is more stable due to its self-aligning acetabular component. 20 The associated modularity also allows the surgeon to balance the soft tissues around the hip and potentially reduces the chances of hip dislocation.…”
Section: Discussionmentioning
confidence: 99%